Stress assessment and management mobile application - Suhairie, Muhammad Afzal; Asmawi, Aziah; Mohd Rum, Siti Nurulain; Mohd Ariffin, Noor Afiza (RMP Publications, 2020)
In the last few years there has been a major increase in mental health awareness in the society. Stress is included as one of the problems in mental health. Stress is common among students in the university. Stress is not a problem, but it can have a major effect on students or anyone if it is not managed properly. This mobile application is developed to help students to understand the stress that they are having better and possibly develop a method to properly manage their stress. The main feature of this mobile application is it can assess the user level of stress by answering a series of questions. This will help users to understand the stress they are facing. Next, it also able to recommend ways to alleviate or manage stress. After answering the question user will be shown some ways to relieve the stress. This mobile application is hope to improve the quality of life of its user.